The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.13057/biodiv/d210514
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on the growth performance of planted Dryobalanops beccarii at reforestation sites after implementation of selective girdling

Abstract: Abstract. Wasli ME, Ambun DB, Kalu M, Sidi M, Nahrawi H, Elias H. 2020. Assessment on the growth performance of planted Dryobalanops beccarii at reforestation sites after implementation of selective girdling. Biodiversitas 21: 1880-1889. This study was conducted to evaluate the growth performance of planted Dryobalanops beccarii Dyer at reforestation sites after silvicultural practices in Gunung Apeng National Park (GANP), Sarawak. The assessed area was planted with D. beccarii in 2005 and undergo silvicultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Approximately 700 hectares of the area had been planted with different types of indigenous species, including Dipterocarps trees such as Dryobalanops beccarii, Shorea parvifolia, and S. macrophylla. The detailed information on the reforestation activities at the study area was reported in our previous study (Wasli et al 2020). The climate is tropical wet (no dry seasons) with subtropical wet forest biozone (Anon 2002).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 700 hectares of the area had been planted with different types of indigenous species, including Dipterocarps trees such as Dryobalanops beccarii, Shorea parvifolia, and S. macrophylla. The detailed information on the reforestation activities at the study area was reported in our previous study (Wasli et al 2020). The climate is tropical wet (no dry seasons) with subtropical wet forest biozone (Anon 2002).…”
Section: Study Areamentioning
confidence: 99%
“…Gunung Apeng National Park (GANP), Sarawak, Malaysia, is one of the sites reforested through enrichment planting (Wasli et al 2020). With the addition of planted indigenous trees into secondary forest areas through enrichment planting, there are abundant food and good breeding ground for various insect pest species (Itoh et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Lambir Hills NP comprises an area of 6949 ha of lowland mixed dipterocarp forests with an average annual rainfall of 2723 mm (1969 2002) (Kume et al 2011), and Gunung Gading NP comprises an area of 5430 ha of lowland mixed dipterocarp forests and lower montane forests with an average annual rainfall of 4095 mm (Lateef et al 2016) (Kenzo et al 2015). Average annual temperature ranges from 23 ℃ in the morning to 33 ℃ in the middle of the afternoon and average annual rainfall is 3500 mm in the Gunung Apeng NP (Wasli et al 2014(Wasli et al , 2020…”
Section: Study Areamentioning
confidence: 99%
“…In the tropics, reforestation is essential in aiding biodiversity recovery by restoring forest cover [5]; ecological rehabilitation to restore high-diversity native tropical forest [6]; improving connectivity in rural landscapes [7], and increasing carbon sequestration for addressing climate change [8]. Several studies have been conducted in Sarawak, Malaysia, to understand the ecological aspects of reforestation activities in tropical rainforests on an experimental basis in relation to various factors [9,10,11]. However, less attention has been made to the effect of early establishment enrichment planting sites in restoring the forest area affected by various land uses.…”
Section: Introductionmentioning
confidence: 99%